INOVASI PASTEL SINGAPURA DENGAN PEMANFAATAN TEPUNG UBI UNGU (Ipomoea batatas) - Yesica Fara Acnelia; Ita Fatkhur Romadhoni; Lilis Sulandari; Qorry’ Aina (JURNAL ILMIAH PENELITIAN MAHASISWA, 2026)
This study was conducted to determine the effect of purple sweet potato (Ipomoea batatas) flour substitution on the sensory quality of Singaporean pastries and to identify the best product and its nutritional content. The research method used was a one-factor completely randomized design (CRD) with three treatment levels: 35%, 45%, and 55% purple sweet potato flour substitution. Sensory quality assessments were conducted by 35 panelists using a 1–5 numerical scale covering the attributes of color, aroma, texture, taste, and overall liking. The test data were analyzed using a one-way ANOVA, followed by Duncan’s multiple range test. The results showed that substituting purple sweet potato flour produced significant differences in the product’s color, aroma, and taste attributes. Based on the sensory evaluation results, the best product was obtained with a 55% substitution of purple sweet potato flour. Proximate analysis of the selected product showed that every 100 g of the product contained 566.40 kcal of total energy, 3.50 g of moisture, 52.67 g of carbohydrates, 37.40 g of total fat, 4.80 g of protein, and 1.65 g of ash. This study indicates that the use of purple sweet potato flour at a 55% substitution level has the potential to produce Singaporean pastries made from local ingredients that possess good sensory quality and adequate nutritional value.